The Application of Communicative Approach in Improving the Students Speaking Ability: A Clasroom Action Research at SMA Negeri 1 Bontonompo Selatan Gowa - Saiful Saiful (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
This research aimed to find out the improvment of the students’ speaking ability through Communicative Approach at the eleventh grade students of SMA Negeri 1 Bontonompo Selatan Gowa. The researcher used Classroom Action Research (CAR). The researcher was conducted two cycles, where each cycle consists of four meetings. The number of subjects of the research were 14 students in class 1B. The researcher got the information from the students’ answers on Speaking text in the form of d-test, test of cycle I and test of cycle II. The application of communicative approach in improving the students’ speaking ability covers speaking accuracy dealing with vocabulary and pronunciation and speaking fluency dealing with smoothness and self-confidence. The mean score of the students vocabulary in d-test was 5.84, and in cycle 1 got 7.72 and in cycle 2 got 8.22 it idicates that the students pronunciation improved significantly. In pronunciation test the d-test (Non CA ), the mean score is 5.18, in cycle I the mean score is 6.74 and in the cycle II, the mean score is 7.38. It indicated that the students’ pronunciation in speaking improved significantly through the application of communicative approach. the mean score of the students’ smoothness in speaking d-test (Non CA ) is 5.18 in the cycle I, the mean score is 6.98 and the cycle II, the mean score is 7.58, It indicates that the students’ smoothness in speaking improved significantly through the application of communicative approach. In speaking fluency dealing with self confidence the result of the students’ speaking d-test (Non CA ) the mean score is 5.72, in the cycle I the mean score is 7.37 and in the cycle II the mean score is 7.92. It indicated that the students’ self confidence in speaking fluency dealing with smoothness was improved significantly through the application of communicative approach. The students’ speaking ability in terms of accuracy and fluency indicates that The mean score of d-test is 5.49, the mean score of cycle I is 7.2 and the mean score of cycle II is 7.77, It proved that the students’ speaking ability in terms of accuracy dealing with vocabulary and pronunciation and fluency dealing with smoothness and self-confidence improved significantly through the application of communicative approach. The students’ attitude toward the application of communicative approach could make the students have strongly positive attitude in improving their speaking ability in terms of accuracy dealing with vocabulary and pronunciation and fluency dealing with smoothness and self confidence by seeing the mean score of the students’ attitude : 42.86 from 14 responds. It means that this method could bring the students to the situation of effective learning in improving the speaking accuracy dealing with vocabulary and pronunciation and speaking fluency dealing with smoothness and self confidence. Having analyzed the data, it can be stated that the students’ reading comprehension at eleventh grade students of SMA Neg. 1 Bontonompo Selatan Gowa is low level before the test in the first cycle and in high level after the test in the second cycle.